Labor resistance against neoliberal challenges to the traditional trade unionism in Turkey: 1986-1991 - Doğan, Mustafa Görkem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
It is a well established tendency to depict the aftermath of the military intervention of 1980 as an era devoid of any significant labor mobilization. This study aims to shed light on the last important cycle of protest led by the organized labor movement spanning from the mid eighties to the beginning of the nineties. This last process of mobilization contains two of the most noteworthy episodes of labor protest, spring actions and the great march of miners to be exact. These two instances from that overlooked era were usually accounted as spontaneous reactions to the deteriorating living conditions of the workers. This study claims that the second part of the eighties witnessed a protest cycle led by the unionized workers and the dynamics of the mobilization can be understood using the political process model of the social movements’ literature. It also argues that the main factor instigating the workers to act was a perceived assault on the moral economy of the industrial relations’ regime of Turkey, existing mostly in the public sector. This moral economy is constructed historically and in a mutual interaction between the state, workers and related political developments in three subsequent periods of the Turkish Republic. Firstly, the late thirties set the pattern of the state led industrialization and the ideological mainframe of the industrial relations; secondly the transition to multi-party politics also determined the circumstances of acceptable union activities and appropriate government responses and finally the introduction of import substitution enlarged the place of the organized labor within the political system. The neoliberal transformation implemented under the Özal administration targeted this moral economy among other things and trade unions mobilized in these circumstances creating one of the most illustrious moments of the Turkish labor history.
Keywords: Social movements -- Turkey.; Labor movement -- Turkey.